(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Adenomyosis is one of the most common gynecological diseases, ranking third after inflammatory processes and uterine fibroids. The urgency of the problem of adenomyosis is due to the severity and versatility of the clinical picture of the disease. At the present stage, it is very important to make a timely diagnosis of the disease. The study of the clinical and anamnestic features of genital endometriosis makes it possible to develop criteria for diagnosis and optimal management of patients with adenomyosis.